2023
DOI: 10.3390/antiox12030554
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Caffeine on Muscle under Lipopolysaccharide-Induced Inflammation

Abstract: Evidence has shown that caffeine administration reduces pro-inflammatory biomarkers, delaying fatigue and improving endurance performance. This study examined the effects of caffeine administration on the expression of inflammatory-, adenosine receptor- (the targets of caffeine), epigenetic-, and oxidative metabolism-linked genes in the vastus lateralis muscle of mice submitted to lipopolysaccharide (LPS)-induced inflammation. We showed that caffeine pre-treatment before LPS administration reduced the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…We aimed to maintain sustained levels of circulating caffeine over an extended period. 44 Additionally, while several studies employ intraperitoneal administration of caffeine, 22,[45][46][47][48] we intended to replicate its consumption as it occurs in real-life scenarios. Considering that humans typically consume caffeine during their most active period, we decided to provide caffeine to mice during their dark period.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to maintain sustained levels of circulating caffeine over an extended period. 44 Additionally, while several studies employ intraperitoneal administration of caffeine, 22,[45][46][47][48] we intended to replicate its consumption as it occurs in real-life scenarios. Considering that humans typically consume caffeine during their most active period, we decided to provide caffeine to mice during their dark period.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that biopterin synthesis and plasma membrane/mitochondrial CoQ reduction pathways suppress lipid peroxide accumulation under cold conditions in parallel with Gpx4. Classically, BH4 is well appreciated as a redox cofactor of several enzymes such as nitric oxide synthase (NOS) and tyrosine hydroxylase (Th), but it has recently been known to affect a wider redox state in cells independently of its role as a cofactor (37, 38). It has been reported that knockdown of Gch1 in an endothelial cell line led to increased ROS production from mitochondria, largely through a NOS-independent effect (39).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that caffeine exerts anti-in ammatory and antioxidant effects by antagonizing adenosine receptors 9,10 . A recent experimental animal study revealed that caffeine was able to decrease levels of pro-in ammatory cytokines and increase the expression of anti-in ammatory cytokines 11 . Another study proved that caffeine could increase the level of adiponectin, reduce the expression of reactive oxygen species (ROS) 12 .…”
Section: Introductionmentioning
confidence: 99%